Wood and leaf anatomy in species of Nahuatlea, Tehuasca, and their sister taxa (Gochnatieae, Asteraceae) - Sandoval-García , Lourdes B.; Terrazas , Teresa; Redonda-Martínez, Rosario; Villaseñor, José Luis (Instituto de Ecología, A.C., 2023)
Background and Aims: In systematic studies the use of anatomical characters is of great relevance to support or refute the circumscription of genera and species. Nahuatlea is a genus of the tribe Gochnatieae (Asteraceae), and includes six species, supported by molecular evidence. However, its anatomical characters have not yet been evaluated from a taxonomic point of view. The objective of this work was to describe the leaf architecture and anatomy as well as the wood anatomy of Nahuatlea species and its sister groups Tehuasca, Anastraphia and Cnicothamnus to evaluate and record attributes with possible systematic value. Methods: Wood and leaf samples from three individuals per species were analyzed using conventional microtechnical techniques to obtain and describe qualitative and quantitative characters. Characters were analyzed using generalized linear mixed models and cluster analysis. Key results: Characteristics of the wood such as porosity, arrangement of the vessels, aperture of intervessel pits and number of series in the rays present possible taxonomic value. For example, vessels with a diagonal pattern are unique to N. hypoleuca, while bi- or triseriate rays are unique to species of Nahuatlea. In the leaf, the venation patterns and the occurrence of hypodermis sheath extensions present possible taxonomic value. The branching veinlets and hypodermis of one layer are exclusive to N. purpusii. The analyses showed significant differences for some of the characters of the wood and the leaf. Conclusions: The anatomy of wood and leaf allows the recognition of unique combinations of characters that support the delimitation of Nahuatlea species.